The Influence Of Promotion, Product Quality And Product Variety On Purchasing Decisions With Brand Image As An Intervening Variable For Herborist Product : Case Study of Solo Raya Student - Sri Darsini; Nur Achmad (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Using brand image as an intervening variable for Herborist prducts, this study examined the impact of promotion, product quality, and product variety on purchasing decisions, This kind of study employs a quantitative methodology. An online questionnaire is used as part of the data collection tool. With a sample siza of 100, the study’s population consisted of Greater Solo students who used Herborist product. Purposive sampling, which selects samples based on predetermined criteria was the sampling strategy employed in this study. Smart PLS is used for data analysis. The study’s finding show that factors related topromotions, product variety, and quality have a favorable and significant impact on consumers’ decisions to buy. It has not been demonstrated that brand image mediates the impact of promotion on purchase decisions. Product quality can have a positive and significant mediating effect on purchasing decisions throught brand image. Product variations can have a positive and significant impact on purchasing decision variables through the mediation of brand image.